TEORI STRUKTUR MODAL : SEBUAH SURVEI - Sujoko, Sujoko (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2007)
This paper explored capital structure theory since 1952 to 1996. The Capital Structure theory firstly introduced by David Duran (1952) to estimate value of the firm. Modigliani and Miller introduced MM-theory and become landmark the capital structure theory because the many paper always referred to the paper. Pecking order theory, Agency Theory and SignalingÂ theory and Dynamic capital structure explained in this paper.